2021
DOI: 10.1177/1747954121993455
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with coach–athlete conversations about mental health in intercollegiate sport

Abstract: Increasing conversation about mental health is one way to decrease stigma and prevent/treat maladaptive processes within the context of sport. Due to their proximity and influence over athletes, coaches can increase conversation and change team culture. The objective of this study was to apply the Theory of Planned Behavior (TPB) to explore the factors associated with coach-athlete conversation about mental health. A total of 136 Canadian coaches completed a demographic questionnaire as well as a TPB-based sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Their attitudes toward mental toughness can either hinder or promote help-seeking behaviors and overall mental health (Mazzer and Rickwood, 2013 ; Moreland et al, 2018 ). Coaches identify the need to support mental health within the scope of their position, which demonstrates an increasing expectation that coaches understand strategies for supporting/developing mental health support (Mazzer and Rickwood, 2013 ; Murphy and Sullivan, 2021 ). An Australian study into coach attitudes found they rarely engaged with young people around mental health concerns (Mazzer and Rickwood, 2013 ).…”
Section: Coaches As a Methods Of Interventionmentioning
confidence: 99%
“…Their attitudes toward mental toughness can either hinder or promote help-seeking behaviors and overall mental health (Mazzer and Rickwood, 2013 ; Moreland et al, 2018 ). Coaches identify the need to support mental health within the scope of their position, which demonstrates an increasing expectation that coaches understand strategies for supporting/developing mental health support (Mazzer and Rickwood, 2013 ; Murphy and Sullivan, 2021 ). An Australian study into coach attitudes found they rarely engaged with young people around mental health concerns (Mazzer and Rickwood, 2013 ).…”
Section: Coaches As a Methods Of Interventionmentioning
confidence: 99%
“…Athletes' psychological quality plays a vital role in their sports career, and sports attitude, as a part of psychological quality, is directly related to athletes' attitude, motivation and final performance in training and competition. In the existing research [ [6] , [7] , [8] ], there are some disputes about the definition of athletes' sports attitude and the choice of measurement tools.…”
Section: Related Workmentioning
confidence: 99%
“…According to Ghani, Zainuddin, Ibrahim, Hashim & Van [53], the depression subscale has 7 question items. Depression with normal (0-9), mild (10)(11)(12), moderate (13)(14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27) and very severe (28-42) levels. The anxiety subscale has 7 question items.…”
Section: Instruments Quantitative Instrumentsmentioning
confidence: 99%
“…[12]. According to Purcell, Gwyther & Rice [13], there were many factors that triggered mental health disorders among athletes, for example overtraining [14], high injury rates, boredom with the training process, problems with the coach [15], teammates/friends, family until low performance [16].…”
Section: Introductionmentioning
confidence: 99%